An exploratory factor analysis of core competencies of public health professionals at primary care service level in Northeastern Thailand. (September 2020) - Leethongdissakul, Songkramchai; Chada, Wilawun; Pengpid, Supa; Chualinfa, Sangud
Background: Public health professionals play a significant role in primary care services in Thailand. Although efforts are being taken to establish professional standards it has neither been outlined nor been officially announced. There is a lack of understanding of what is a suitable set of core competencies for a public health professional. Objectives: This study aimed to explore the core competencies of public health professionals at the primary care service level in Thailand. Methods: A quantitative survey using a questionnaire was conducted in 862 public health professionals in the northeast of Thailand. Exploratory factor analysis was applied to develop a tool to test the competencies of public health professionals. Results: The results revealed core competencies in the following five main proficiencies: (1) public health administration and laws; (2) disease prevention and control; (3) social and environmental determinant of health and health research; (4) health promotion and community; and (5) basic medical care, screening, and diagnosis. In addition, the five core competencies included 50 items suitable for this sample. These factors accounted for 71.90% of the variance. Conclusion: In conclusion, this study's finding provides significant recommendations to policymakers to improve and initiate a new policy or a standard guideline for public health education and human resource for health production and management in Thailand.